Accounting Practices of Small and Medium Enterprises (SMEs): A Comparative Study - Akter, Morium; Alam, Kazi Monirul (Feni University Journal, 2026)
This study examines accounting practices in Feni Sadar Upazila compared to other upazilas, focusing on small and medium-sized enterprises (SMEs). It investigates the types of accounting records maintained, the relationship between accounting recordkeeping status and factors such as business duration, size, and ownership structure, the challenges SMEs face in maintaining accurate books and to explore the suggestions to improve account record keeping status provided by SMEs in Feni District. The research is empirical, utilizing a structured questionnaire. The findings indicate a statistically significant difference in accounting record-keeping status between Feni Sadar Upazila and others. However, no significant relationship was found between accounting practices and business size or duration. In contrast, a significant relationship was noted between record-keeping status and ownership structure. Respondents moderately agreed with several challenges faced, including difficulties in separating business expenses, identifying all expenses, stating actual revenue, and completing accounting records. To address these challenges, they suggested solutions such as ongoing workshops, professional training, effective internal controls, and free accounting services. Overall, this research contributes valuable insights to the literature on SMEs and aids regulatory agencies in improving accounting practices within the sector, ultimately supporting the growth and sustainability of SMEs in Feni District. FENI UNIVERSITY JOURNAL, 2025, 4(1), PP. (67-92)